RNF138 contributes to cisplatin resistance in nasopharyngeal carcinoma cells - Hangyu Xu; Qing Yin; Linna Fan; Yating Zhao; Biying Song; Qifan Xu; Jie Zhu; Meifen Xu (Scientific Reports)
Abstract Resistance to chemotherapy is a significant concern in the treatment of nasopharyngeal carcinoma (NPC), and occurs due to various mechanisms. This study is aimed to evaluate the effects of RING finger protein 138 (RNF138) in the development of cisplatin resistance to NPC. After gene overexpression and silencing, the expression levels of RNF138 were evaluated. The impacts of RNF138 on the proliferation and apoptosis rate of NPC cells were then assessed. γ-H2AX-mediated DNA damage was determined via immunofluorescence assay. Moreover, a tumor xenograft mouse model was developed to investigate the role of RNF138 on NPC progression in vivo. Additionally, transcriptome analysis was performed in 5–8 F cells transfection with OE-RNF1138 or OE-NC.Cisplatin significantly inhibited the proliferation, and promoted apoptosis and DNA damage in NPC cells; however, overexpression of RNF138 reversed the aforementioned regulatory role of cisplatin on NPC cells. Knockdown of RNF138 resulted in contrasting phenotypic outcomes. Additionally, in nude mice, RNF138 overexpression attenuated the suppressive effects of cisplatin on the growth of xenograft tumor, while RNF138 silencing further enhanced the inhibiting role of cisplatin. We further indicated that in 5–8 F cells following RNF138 overexpression, some pathways such as PI3K-Akt signaling pathway, human papillomavirus infection and ErbB signaling pathway that have been reported to be associated with NPC progression and cisplatin resistance were significantly enriched. These findings indicate that the modulation of RNF138 could potentially address the issue of chemotherapy failure by overcoming cisplatin resistance in NPC cells, making it a promising candidate for targeted drug therapy.